Carrier design based on zein: From the perspectives of multi-molecule encapsulation, probiotic encapsulation, and application standards - Defeng Shu; Yueyue Liu; Jinlong Xu; Yongkai Yuan (Current Research in Food Science)
Zein is an excellent carrier material for active substances. Previous reviews have mainly focused on the encapsulation of single active molecules, while this review is for the first time to comprehensively review the design of multi-molecules and probiotics carriers, and summarize its application standards. For multi-molecule encapsulation, zein nanoparticles with core-shell structure are widely used. Based on the difference in fabrication methods and physicochemical properties of active molecules, zein nanoparticles were categorized into mixed/isolated encapsulation. Besides, zein microparticles and Pickering emulsions (with two-compartment structures for different active molecules) stabilized by zein nanoparticles as multi-molecule delivery platforms are also discussed. For carrier design of probiotics, the methods include layer-by-layer self-assembly/complex coacervation based on zein nanoparticles, microcapsules, emulsion, and probiotic biofilm formation based on zein fibers. Importantly, zein has different criteria in the food/pharmaceutical industry, which is a prerequisite for practical application. Although zein-based multi-molecule carriers have been studied extensively, most of the current work focuses on characterizing properties instead of mechanism investigation of complex systems. In the future, designing carriers with superior structures to control the release rate of different molecules and targeted colonic delivery of probiotics are the main challenges for expanding zein applications. This review is expected to guide the rapid and scientific progress of zein-based carrier design for multi-molecules and probiotics.